HUBUNGAN MEMBANGUN KEHARMONISAN KELAS: PERAN TEKNOLOGI DALAM PEMBELAJARAN YANG POSITIF - Andini Putri Kusuma; Ilmi Fitri Islami; Septia Anggraini; Maysa Nurarisanty; Daffa Anugerah Putra; Fandyo Bariq Ramadhani Johan Purwanto (Counseling Milenial (CM), 2024)
In this research, the author is interested in analyzing more deeply the importance of the role of a positive school environment, which is very important in supporting the learning process and classroom management. The purpose of this article is to explore more deeply how a positive environment can support learning and effective classroom management. This research is field research using a qualitative approach. Observations show that effective classroom management is essential to creating a positive learning environment that increases student comfort and motivation. A supportive environment increases student concentration and engagement, and motivates teachers to teach better.